Human immunodeficiency virus/acquired immune deficiency syndrome antiretroviral therapy initiated on the same day in treatment-naïve people with human immunodeficiency virus: A comparative study of efficacy and regimen - Jing Yuan; Changgang Deng; Qisui Li; Yanyu Sun; Wei Huang; Wei Zhang; Min Liu; Yanjie Yin (Chinese Medical Journal)
Abstract. Background:. Rapid initiation of antiretroviral therapy (ART) is recommended by guidelines, however, real-world studies of same-day initiation of ART in China are limited, and an optimal treatment regimen has yet to be identified. The study aims to provide a realistic reference for rapid initiation of ART. Methods:. We retrospectively analyzed the clinical data of treatment-naïve people with human immunodeficiency virus (PWHs) who were diagnosed and prescribed same-day ART initiation from January 1, 2021 to December 31, 2022 at Chongqing Public Health Medical Center. PWHs voluntarily chose an ART regimen that divided them into two groups: National Free Antiretroviral Treatment Program (NFATP)-recommended regimens group (2 nucleoside reverse transcriptase inhibitors + non-nucleoside reverse transcriptase inhibitors/protease inhibitors) and bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) group. The primary endpoint was the virological outcome of the two groups for same-day ART initiation at 24 weeks and 48 weeks. The secondary endpoints included changes in CD4 counts, maintenance of the original ART regimen at 48 weeks, and lipid levels and renal function at 48 weeks. Results:. A total of 255 PWHs were included in the study, including 131 (51.4%) in the NFATP group and 124 (48.6%) in the BIC/FTC/TAF group. The overall virological suppression rates at 24 weeks and 48 weeks were 78.2% (165/211) and 95.4% (207/217), respectively. At 24 weeks, the virologic suppression rate in the NFATP group was lower than that in the BIC/FTC/TAF group (65.3% [66/101] vs. 90.0% [99/110], P <0.001). The median increase in the CD4 count was 198.0 (126.0–300.0) cells/μL at 24 weeks, with 182.0 (108.0–245.0) cells/μL in the NFATP group and 219 (132.0–316.0) cells/μL in the BIC/FTC/TAF group (P = 0.035). At 48 weeks, there was no significant difference in the virological suppression rate or CD4 count between the groups. The 48-week initial ART regimen retention rates and treatment retention rates were significantly higher in the BIC/FTC/TAF group than in the NFATP group (91.1% (113/124) vs. 71.8% (94/131), 99.2% (118/119) vs. 93.0% (120/129), respectively). In terms of safety, there were no significant changes from baseline in levels of creatinine, estimated glomerular filtration rate (eGFR), or lipids in either group at 48 weeks. Conclusions:. ART initiation on the day of diagnosis is effective, safe, and feasible, with satisfactory rates of virologic suppression, 48-week initial ART regimen retention rates, and treatment retention rates in treatment-naïve PWHs. In our study, the early virologic suppression rate, CD4 cell counts, and treatment retention of the BIC/FTC/TAF regimens were significantly better than those of the NFATP regimens.